2015
DOI: 10.1007/s13246-015-0367-0
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo and experimental internal radionuclide dosimetry in RANDO head phantom

Abstract: Monte Carlo techniques are widely employed in internal dosimetry to obtain better estimates of absorbed dose distributions from irradiation sources in medicine. Accurate 3D absorbed dosimetry would be useful for risk assessment of inducing deterministic and stochastic biological effects for both therapeutic and diagnostic radiopharmaceuticals in nuclear medicine. The goal of this study was to experimentally evaluate the use of Geant4 application for tomographic emission (GATE) Monte Carlo package for 3D intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
(24 reference statements)
1
2
0
Order By: Relevance
“…The assessment of the curves plotted in Figure 3 also confirmed that the organ geometry (such as size and shape), density, and the inter-organ distance have a significant influence on the photon cross-irradiation SAF values (14).…”
Section: Safs For Photon Energysupporting
confidence: 52%
“…The assessment of the curves plotted in Figure 3 also confirmed that the organ geometry (such as size and shape), density, and the inter-organ distance have a significant influence on the photon cross-irradiation SAF values (14).…”
Section: Safs For Photon Energysupporting
confidence: 52%
“…MOSFET (14) Although several articles published in 2015 have received citations to date in Web of Science [13][14][15][16][17][18][19][20][21][22][23][24] or Scopus [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] it was considered insufficient time to represent citation trends of more mature articles amongst the various categories.…”
Section: A Citation Analysis Of Articles Published In Australas Physmentioning
confidence: 99%
“…Therefore, we usually need to detect the dose of radiation received by people or objects in areas such as space travel, medical care and environmental moni toring. Several kinds of dosimeters have been explored such as thermo luminescent dosimeters (TLDs) [2], semiconductor diodes [3] and optically stimulated luminescence dosimeters (OSDLs) [4]. However, most of them are not suitable for working in space, as they do not meet the requirements of being of low weight and small size, as well as able to work following exposure to high doses.…”
Section: Introductionmentioning
confidence: 99%